An annotated checklist of the free-living nematodes from mangrove thickets of Vietnam - Gagarin, Vladimir G. (Zootaxa, 2018)
This article presents an annotated list of nematode taxa found in mangrove forests along four Vietnamese rivers: the Mekong, Be, Red and Yen Rivers. The list includes 208 species belonging to 88 genera, 36 families and 11 orders of the phylum Nematoda. Three genera and 138 species were first described from these habitats as new taxa. Theristus orientalis Gagarin, Nguyen Vu Thanh, 2005 is transferred to the genus Daptonema Cobb, 1920 as D. orientale (Gagarin, Nguyen Vu Thanh, 2005) nov.nom.. based on the presence of three terminal caudal setae.